Save the last dance - Cort, Robert W.; Madden, David, 1955-; Adler, Duane G.; Edwards, Cheryl; Carter, Thomas A., 1955-; Stiles, Julia, 1981-; Thomas, Sean Patrick; Kinney, Terry; Paramount Pictures Corporation (1914-1927); MTV Films (Firm) (Hollywood, CA : Paramount, 2001)
When her mother suddenly dies, Sara must abandon her plans to become a ballerina and join her estranged father on Chicago's gritty South side. She feels out of place until she is befriended by a black classmate and her handsome brother, Derek. Sara and Derek's shared love for dance leads to romance-- and opposition from their families and friends.
Widescreen.
Special features: audio commentary by director Thomas Carter; deleted scenes; The making of "Save the Last Dance"; cast and crew interviews; music video "Crazy" by K-Chi & Jo Jo; theatrical trailer.
Director of photography, Robbie Greenberg ; editor, Peter E. Berger ; music, Mark Isham ; choreographer, Fatima.
Julia Stiles, Sean Patrick Thomas, Terry Kinney, Fredro Starr.
Rated PG-13.
DVD.
Keywords: Hip-hop -- Drama; Ballet dancing -- Drama; Feature films; Films for the hearing impaired